2009
DOI: 10.1002/stem.5530150739
|View full text |Cite
|
Sign up to set email alerts
|

The chernobyl governmental program: Two years of experience at the belarusian bone marrow transplant centre

Abstract: The Bone Marrow Transplantation Program in Belarus was founded in 1992, and in 1993, a Bone Marrow Transplantation Centre was created in Minsk. From February 1994 to April 1996,19 allogeneic bone marrow, 16 autologous bone marrow and 10 autologous peripheral blood stem cell transplantations were performed. Reasons for transplantation included chronic myeloid leukemia, multiple myeloma, severe aplastic anemia, acute myeloid leukemia, acute lymphoblastic leukemia, progressive myelofibrosis, Hodgkin's disease, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…To reduce the periods of profound neutropenia, thrombocytopenia and anemia, hematopoietic cell transplantation has been used in clinical settings as well as in a limited number of recent radiological accidents (44, 49). The major complication of allogeneic hematopoietic cell transplantation is graft versus host disease (GVHD) due to alloreactive donor T lymphocytes causing potentially life-threatening normal tissue damage.…”
Section: Hematopoietic System: Animal Models For the Bone Marrowmentioning
confidence: 99%
“…To reduce the periods of profound neutropenia, thrombocytopenia and anemia, hematopoietic cell transplantation has been used in clinical settings as well as in a limited number of recent radiological accidents (44, 49). The major complication of allogeneic hematopoietic cell transplantation is graft versus host disease (GVHD) due to alloreactive donor T lymphocytes causing potentially life-threatening normal tissue damage.…”
Section: Hematopoietic System: Animal Models For the Bone Marrowmentioning
confidence: 99%
“…[14] However, several publications were against the findings. [15][16][17][18][19] Discordant reports on the null effect of exposure and leukemogenesis have been published. [15][16][17][18][19] …”
Section: Thyroid Cancermentioning
confidence: 94%
“…Some reports have noted the increased incidence. [19][20][21] Tondel et al, have noted 'a continuous increase of brain tumor incidence in children, in the age group of 0 -19 years, during the period 1978 -1992, without a clear relationship to the Chernobyl fallout.'. [20] LUNG CANCER Another malignancy that is widely studied is lung cancer.…”
Section: Brain Cancermentioning
confidence: 97%
“…The best technique is still bone marrow transplantation, which is limitedly available in large medical center. According to a report in the post Chernobyl crisis, Uss et al reported their experience that ''There was nothing unusual about the post-transplantation period [12].'' The complications are graft-versus-host disease, septic shock, veno-occlusive disease, bleeding and intestinal pulmonary fibrosis [12].…”
Section: Treatment Of Multiple Myeloma In Post Nuclear Crisismentioning
confidence: 99%